Migraine in 746 patients with multiple sclerosis - Yara Dadalti Fragoso; Tarso Adoni; Soniza V. Alves-Leon; Samira L. Apostolos-Pereira; Marcos A. Diniz Carneiro; Edila M. Chikota; Denise Sisterolli Diniz; Audred C. B. Eboni; Sidney Gomes; Marcus Vinicius M. Gonçalves; Ricardo Pereira Goncalves; José Luiz Inojosa; et al. (Arquivos de Neuro-Psiquiatria)
ABSTRACT Migraine adds to the burden of patients suffering from multiple sclerosis (MS). The ID-migraine is a useful tool for screening migraine, and the Migraine Disability Assessment questionnaire can evaluate disease burden. The aim of the present study was to assess the presence and burden of migraine in patients with MS. Methods: Patients diagnosed with MS attending specialized MS units were invited to answer an online survey if they also experienced headache. Results: The study included 746 complete responses from patients with MS and headache. There were 625 women and 121 men, and 69% of all the patients were aged between 20 and 40 years. Migraine was identified in 404 patients (54.1%) and a moderate-to-high burden of disease was observed in 68.3% of the patients. Conclusion: Migraine is a frequent and disabling type of primary headache reported by patients with MS.